2019
DOI: 10.12693/aphyspola.136.310
|View full text |Cite
|
Sign up to set email alerts
|

Microplasma Deposition of Biocompatible Coatings Using an Intelligent Robotic System for Plasma Processing

Abstract: This paper presents the method of microplasma deposition of biocompatible coatings using an intelligent robotic system for plasma processing. The two-layer coatings from biocompatible materials, namely from titanium wire and hydroxyapatite powders are sprayed on the surface of titanium substrates. The synthesis of hydroxyapatite powder suitable for applying biocompatible coatings onto medical implants is provided by chemical precipitation. Optimization of the synthesis parameters is carried out by the mathemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The production and research site, where experimental medical implants from titanium alloys are manufactured by CNC machines, operates at D. Serikbayev East Kazakhstan Technical University [18,20,21]. Titanium alloys are the preferred material for the production of orthopedic and dental prostheses.…”
Section: Materials and Research Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The production and research site, where experimental medical implants from titanium alloys are manufactured by CNC machines, operates at D. Serikbayev East Kazakhstan Technical University [18,20,21]. Titanium alloys are the preferred material for the production of orthopedic and dental prostheses.…”
Section: Materials and Research Methodsmentioning
confidence: 99%
“…The use of robotic MPS allows for precision coating deposition on complex-shaped implant parts, such as parts of elbow and hip replacements. In our previous papers [18][19][20][21][22], it was shown that robotic microplasma spraying can produce coatings on medical implants made of biocompatible titanium and hydroxyapatite materials with the desired porosity and roughness, meeting the requirements of international standards for implants for surgery in terms of coating adhesive strength [23], crystallinity and purity [24].…”
Section: Introductionmentioning
confidence: 99%
“…3D scanning and AM technologies facilitate the fabrication of custom-designed implants with complex geometries, and robotic plasma spraying is used for coating. The authors of this review article have experience with successful robotic MPS of biocompatible titanium and HA coatings onto CNC-machined titanium alloy orthopedic implants [33][34][35]97] and on trabecular surfaces of additively manufactured titanium implants (particularly by the SLM method) [19].…”
Section: Thermal Plasma Spraying Of Metal-ceramic Coatingsmentioning
confidence: 99%
“…Varying MPS parameters following the matrix of the factorial experiment make it possible to select a combination of spraying parameters that ensures the formation of coatings with specified porosity values [22,23]. The use of a robotic MPS allows for the precise spraying of coatings on implants of complex shapes, moving the plasma source at a constant modulus speed along a 3D trajectory along the surface of the implant with precise adherence to the spraying distance and a plasma jet perpendicular to the surface [23,33]. Previous papers [22,34] have shown that by using robotic microplasma spraying of commercially pure titanium and hydroxyapatite coatings on medical titanium implants, it is possible to obtain coatings with the desired levels of porosity and roughness and satisfactory adhesion to the substrate, including coatings with 95% purity and 90% crystallinity from hydroxyapatite on 3D-printed trabecular Ti6Al4V alloy substrates.…”
Section: Introductionmentioning
confidence: 99%